Exploration Of Ancient History Of Kashmir And Prevailed Literature Under The Hindu Rulers (Journal of Namibian Studies : History Politics Culture, 2023)
Kashmir has a hundreds of years’ history. This study’s main aim is to explore the ancient history of the great Kashmir and to look into the prevailed literature during the Hindu Ruler. The exploration of the ancient history of Kashmir unveils a captivating narrative of cultural and literary splendor, particularly during the epochs of Hindu rule. Spanning from the Maurya and Gupta periods to the ascendancy of the Karkota dynasty, Kashmir evolved into a crucible of intellectual and artistic fervor. This research delves into the profound impact of Hindu rulers on the literary landscape of Kashmir, focusing on the patronage of Sanskrit as the classical language and the resultant flourishing of diverse literary works. A qualitative study led out by focusing the book “"Kashmir: A Tapestry of Time - Tracing the Footprints of Hindu Rule”. A keen insight was given to explore the ancient history and the literature during Hindus rulers. The future researchers are recommended to explore more aspects about the great Kashmir’s History.